Workplace Mental Health Interventions in India: A Rapid Systematic Scoping Review - Pandya, Apurvakumar; Khanal, Niharika; Upadhyaya, Mudita (Frontiers in Public Health, 2022)
The mental health initiatives at the workplace are growing in numbers over the past few years. Public and private sectors continue to explore avenues to navigate and adapt initiatives to promote employee's mental wellbeing. However, such initiatives in the Indian context are not thoroughly studied. We attempted to review existing literature on workplace mental health interventions in the Indian context. The scoping review was conducted following the standard process as recommended by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for scoping reviews. We searched in the databases such as PubMed, Google Scholar and Scopus. Scientific literature including gray literature of the past decade was searched to synthesize evidence on types of mental health interventions and their unique features. Of the 1,311 records, 30 records that met the inclusion criteria were included for the final review. The review highlights evidence on stress and mental health problems faced by the working population and various strategies adopted by organizations to address mental health problems. However, very few interventions were accompanied by comprehensive needs assessment, impact evaluation and workplace policy initiatives. Most interventions were curative–provisioning counseling services, limiting the scope of mental health promotion activities. Addressing mental health wellbeing comprehensively and aligning an organization's policies are crucial. Research on employee mental health, its risk factors, and cost-effectiveness analysis of workplace mental health interventions in the Indian context need to be prioritized.